New entrepreneurship policy and the encounter between policy implementers and entrepreneurs - a case study from Finland. (1st January 2015) - Niska, Miira; Vesala, Kari Mikko
Both the new regional policy and the new entrepreneurship policy aim to establish public–private partnerships to generate global competitiveness. Previous studies, however, have indicated that the relationship between public policy implementers and entrepreneurs is not trouble–free. This paper explores the construction of partnership, or co–agency, between local policy actors and entrepreneurs by analysing a case of Finnish food industry cluster promotion. The analysis demonstrates how co–agency can be achieved when both parties position themselves and each other as agents serving third party principals who share similar interests. However, the entrepreneurship policy implementation may also face novel relational challenges stemming from the objection of local communities and the denial of the partnerships' legitimisation.